Geometria Lipschitz ambiente das superfícies normalmente mergulhadas - Medeiros, Davi Lopes Alves de (2023)
In this paper, it is studied ambient Lipschitz geometry of defi nable surfaces in a polynomially bounded o-minimal structure over the reals, with emphasis on semialgebraic surfaces. We show that if a semialgebraic, normally embedded surface germ in R3 has a simple link, that is, isomorphic to either a segment or a circle, then such surface is ambient bi-Lipschitz equivalent to a Hölder triangle in the fi rst case, or to a horn in the second case.